BUDAYA TA‘ZȊR BIL MȂL DALAM LUNGKUNGAN PESANTREN: DALAM PERSPEKTIF ULAMA KONVENSIONAL - Qosim Khoiri Anwar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Jarȋmah ta'zȋr are criminal acts that have not been determined by the legal sanctions Personality ', but a stipulation submitted to the judge / government (ulil amri). The intent and purpose of punishment ta'zir is to educate the offender to be a deterrent. Ta'zir bil mȃl is one part of jarȋmah ta'zȋr form of punishment, ie the punishment imposed by the judge / government (ulil amri) against perpetrators jarȋmah (criminal offense), by taking the wealth jarȋmah actors. Although the intent and purpose of the enactment of this sentence is to educate the offender. but it is becoming a dilemma for property taken was not known clearly and definitely on the utilization and usage. This raises a very sharp differences among scholars about whether authorized or imposed such a punishment is motivated ini.Penelitian the discrepancy between theory and practice concepts that occur, and to describe the views of legal scholars ta'zȋr bil mȃl to determine the underlying reasons. This research is a library (library research) that is descriptive qualitative. Collecting data in this study using techniques of documentation. The technique of analysis in this study is qualitative using deductive reasoning. The results showed that the law ta'zȋr bil mȃl by scholars there are differences of opinion are allowed, with a record of property taken was not meant to be privately owned by the judges / government itself, but the treasure was returned to its owner after he promised not reiterates does (repent), and prohibits (absolutely not allowed) to punish the offenders took possessions jarȋmah (ta'zir bil mȃl), because it is not permissible for someone taking someone else's property without legal cause is based, it is an unjust act or false. For the judge / government returned to the intention respectively. Because the intent and purpose of the penalty is intended to educate and deter perpetrators jarȋmah (criminal act) in order not to repeat back in his actions, not menzaliminya.